ANALISIS STATUS MUTU AIR SUNGAI KARANG MUMUS SEGMEN JEMBATAN S. PARMAN DAN JEMBATAN PERNIAGAAN KOTA SAMARINDA - Rini Ariesa Puspa; Vita Pramaningsih; Andi Daramusseng (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2023)
Karang Mumus is a river that is widely used by the community for various activities to meet the needs of life such as bathing, washing and as a source of drinking water. This causes water quality to decline and results in health impacts on river users. The purpose of this study was to analyze the water quality status of the Karang Mumus River Segment of the S. Parman Bridge and the Perniagaan Bridge of Samarinda City. This research is an observational descriptive study, which is to find out what are the potential sources of pollution in river water, find out how the quality of river water is using the Pollution Index method and find out the health impacts caused by river water. The research shows that the sources of pollution in the S. Parman Bridge and Perniagaan Bridge segments come from household and industrial activities. The status of river water quality in the S. Parman Bridge and Perniagaan Bridge segments has light and heavy polluted categories with 4 parameters that do not meet the quality standards, namely, TSS, COD, DO, and Fecal Coli. The health impacts caused by using river water in the S. Parman Bridge segment and Perniagaan are diarrhea, dysentery and skin irritation. The largest percentage of diseases experienced by the people of the river area of the S. Parman Bridge segment is diarrhea by 30%, while in the Perniagaan Bridge segment, skin irritation is 40%. Keywords: Karang Mumus River; Pollution Index; Water Quality